Supervised exercise delivered via telehealth in real time to manage chronic conditions in adults: a protocol for a scoping review to inform future research in stroke survivors. Issue 3 (20th March 2019) - Ramage, Emily R; Fini, Natalie A; Lynch, Elizabeth A; Patterson, Amanda; Said, Catherine M; English, Coralie
Abstract : Introduction: Increasing physical activity reduces secondary stroke risk factors, but many stroke survivors have low levels of physical activity. Supervised exercise delivered via telehealth has the potential to overcome barriers to increased physical activity in stroke survivors. Our scoping review will examine the emerging field of supervised exercise delivered via telehealth to map the available evidence in relation to its efficacy, acceptability, safety and feasibility in chronic conditions to inform future research into its ability to increase physical activity. Methods and analysis: The methodological framework of Arksey and O'Malley will be applied to our scoping review. A systematic search of Medline, CINAHL, Scopus, Cochrane, Pedro and Embase; hand searching of pertinent studies' reference lists; and consultation with experts in the field will identify relevant papers. Studies involving participants with a chronic condition who undertake supervised exercise delivered by a health professional via telehealth targeted at improving secondary stroke risk factors or involving lower limb weight-bearing exercise will be included. Study selection and critical appraisal of individual studies will be carried out independently by two authors with discrepancies resolved by a third author. Quantitative and qualitative data will be charted using a standardised form. Results will be tabulated and narratively summarised to highlight findings relevant to the review's research questions and to inform recommendations for future research. Ethics and dissemination: Our review will significantly contribute to the knowledge base of exercise and rehabilitation delivered via telehealth and its application in chronic conditions, including stroke. Findings will be relevant to researchers, healthcare workers and policy-makers and will be disseminated through publication and presentations. Only secondary deidentified data will be included, therefore ethics approval will not be sought. This protocol is not registered as PROSPERO currently excludes scoping reviews.